Distinct Expression Patterns of Osteopontin and Dentin Matrix Protein 1 Genes in Pituitary Gonadotrophs - Bjelobaba, Ivana; Janjic, Marija M.; Prévide, Rafael Maso; Abebe, Daniel; Kucka, Marek; Stojilkovic, Stanko S. (Frontiers in Endocrinology, 2019)
Cell-matrix interactions play important roles in pituitary development, physiology, and pathogenesis. In other tissues, a family of non-collagenous proteins, termed SIBLINGs, are known to contribute to cell-matrix interactions. Anterior pituitary gland expresses two SIBLING genes, Dmp1 (dentin matrix protein-1) and Spp1 (secreted phosphoprotein-1) encoding DMP1 and osteopontin proteins, respectively, but their expression pattern and roles in pituitary functions have not been clarified. Here we provide novel evidence supporting the conclusion that Spp1/osteopontin, like Dmp1/DMP1, are expressed in gonadotrophs in a sex- and age-specific manner. Other anterior pituitary cell types do not express these genes. In contrast to Dmp1, Spp1 expression is higher in males; in females, the expression reaches the peak in response during the diestrus phase of estrous cycle. In further contrast to Dmp1 and marker genes for gonadotrophs, the expression of Spp1 is not regulated by gonadotropin-releasing hormone in vivo and in vitro. However, Spp1 expression increases progressively after pituitary cell dispersion in both female and male cultures. We may speculate that gonadotrophs signal to other pituitary cell types about changes in the structure of pituitary cell-matrix network by osteopontin, a function consistent with the role of this secretory protein in postnatal tissue remodeling, extracellular matrix reorganization after injury, and tumorigenesis.